Sosialisasi Kolaborasi Inovatif Dengan Samsat Dalam Peningkatan Kesadaran dan Kepatuhan Pajak di Kota dan Kabupaten Sukabumi Bagi Wajib Pajak Pemula - Idang Nurodin; Fitriani Fitriani; Hani Handayani; Hanny Maulia Yusup; Irna Destiana Yusuf; Sri Mulyani; Syifa Rahadatul Aisyi (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Increasing tax awareness and compliance among the younger generation is key to expanding the regional tax base and supporting sustainable development. Through the Independent Learning Community Service Program (KKN MBKM), the University of Muhammadiyah Sukabumi, in collaboration with the Sukabumi Tax Administration and Tax Office (P3DW SAMSAT), conducted a Motor Vehicle Tax (PKB) outreach program for high school students as first-time taxpayers. This activity was conducted in four schools in Sukabumi Regency using an educational and interactive approach, including facilitator training, observation, digital material development, and technology-based quizzes. Results demonstrated high participant enthusiasm, increased understanding of tax obligations, and increased utilization of digital regional tax services. This program not only impacted public tax literacy but also provided contextual field experience for students. This synergy between educational institutions and government agencies provides an effective collaborative model for developing a tax-conscious and socially responsible young generation.